2009
DOI: 10.1021/ja9058052
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Propensities of Amino Acid Residues in GxG Peptides Inferred from Amide I′ Band Profiles and NMR Scalar Coupling Constants

Abstract: A reliable intrinsic propensity scale of amino acid residues is indispensable for an assessment of how local conformational distributions in the unfolded state can affect the folding of peptides and proteins. Short host-guest peptides, such as GxG tripeptides, are suitable tools for probing such propensities. To explore the conformational distributions sampled by the central amino acid residue in these motifs, we combined vibrational (IR, Raman, and VCD) with NMR spectroscopy. The data were analyzed in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
327
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(364 citation statements)
references
References 96 publications
31
327
6
Order By: Relevance
“…Different kinds of vibrational spectroscopy have been used in combination to analyze the mixed spectra that result when bands from individual backbone conformers are not resolved but instead are superimposed (20,21). Hopefully this type of analysis can be tested in future work by comparison with the dipeptide results reported here.…”
Section: Estimation Of Errors and Comparison With Literature Resultsmentioning
confidence: 99%
“…Different kinds of vibrational spectroscopy have been used in combination to analyze the mixed spectra that result when bands from individual backbone conformers are not resolved but instead are superimposed (20,21). Hopefully this type of analysis can be tested in future work by comparison with the dipeptide results reported here.…”
Section: Estimation Of Errors and Comparison With Literature Resultsmentioning
confidence: 99%
“…Interestingly, studies of the alanine dipeptide in vacuo are conclusive in discarding the right-handed α-helix (αR) or the polyproline II (PII) conformations as low energy minima. This is an intriguing result since the former is often found in helical parts of globular proteins [19] and the latter is known to be the most abundant structure found in solution [20]. This result suggests that the environment created by either the rest of the protein or the solvent substantially modifies the conformational profile of the molecule.…”
Section: Introductionmentioning
confidence: 92%
“…Results from a recent structural analysis of a more limited set of GxG peptides (x = A, V, L, E, F, S, M, K), which quantitatively explored the entire conformational ensemble of the respective x residue, seem to point into the same direction, revealing only a very limited sampling of regions associated with helical, b-turn (excluding serine) and g-turn conformations. [6] However, this study did not include the above-mentioned turn-promoting residues, namely D, N, T, and C. MD simulations mostly suggest a statistical coillike distribution of nearly all amino acid residues in unfolded peptides (with the exception of P), and thus imply that they can sample the entire sterically allowed region of the Ramachandran plot. [22] Moreover, this study did not indicate any turn propensities for specific amino acids.…”
Section: Introductionmentioning
confidence: 96%
“…[3] This is the case for alanine, for which recent spectroscopic studies have convincingly shown an exceptionally high propensity to adopt poly-A C H T U N G T R E N N U N G proline II (PPII)-like conformations. [4][5][6] Other amino acid residues with predominantly aliphatic or aromatic side chains (e.g., L, K, V, F, M) exhibit a more balanced distribution of conformational sampling in the upper-left quadrant of the Ramachandran plot, which encompasses PPII and different types of b-strand-like structures. [7,8] The propensity for helical structures is rather low for all of these residues, which, particularly for alanine, is at variance with predictions from molecular dynamics (MD) simulations using a variety of different force fields.…”
Section: Introductionmentioning
confidence: 99%